1998
DOI: 10.1063/1.122050
|View full text |Cite
|
Sign up to set email alerts
|

Model of leakage characteristics of (Ba, Sr)TiO3 thin films

Abstract: We have investigated the dependence of leakage current and capacitance of Pt/Ba0.5Sr0.5TiO3/Pt capacitors on annealing temperature under high vacuum conditions. It is observed that leakage currents increase asymmetrically for negative and positive bias voltage with increasing annealing temperature. A model of leakage current and capacitance characteristics has been proposed on the assumption of generation of oxygen vacancies by annealing at the interfaces of the dielectric film adjacent to the Pt electrodes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 5 publications
5
39
1
Order By: Relevance
“…The leakage current characteristics are distinctly different in the range of higher dc fields, both in the positive and negative voltage region. This may be caused by generation of a different amount of oxygen vacancy at the top Au/BTS interface and at the bottom Pt/BTS interface [15]. The asymmetry between the positive and negative voltage parts of the J-V characteristic could be attributed to oxygen vacancies and movable ions at the top Au/BTS interface and the bottom LNO/BTS interface [15,16], which is consistent with the C-V results.…”
Section: Resultssupporting
confidence: 83%
“…The leakage current characteristics are distinctly different in the range of higher dc fields, both in the positive and negative voltage region. This may be caused by generation of a different amount of oxygen vacancy at the top Au/BTS interface and at the bottom Pt/BTS interface [15]. The asymmetry between the positive and negative voltage parts of the J-V characteristic could be attributed to oxygen vacancies and movable ions at the top Au/BTS interface and the bottom LNO/BTS interface [15,16], which is consistent with the C-V results.…”
Section: Resultssupporting
confidence: 83%
“…In Fig. 3, it is also indicated that the dielectric loss of the BST thin films decreased with the increasing in Ca content, which is consistent with the result of the leakage current shown in [16].…”
Section: Methodssupporting
confidence: 93%
“…This has helped to elucidate the effects of microstructures on the device performance. The effects of oxygen vacancies on electrical properties such as low-frequency dielectric relaxation and electric conduction, 20 I-V and C-V characteristics of metalferroelectric-semiconductor field-effect transistors ͑MFSFETs͒, 21 and leakage current 22 have also been simulated.…”
Section: Introductionmentioning
confidence: 99%